Etika perang dalam al-qur’an:Studi kasus ayat-ayat tentang ash’hur al-ḥurum - Sayyida, Sayyida; Abolfazl Tajik (Yayasan Insanulhaq, 2025)
Ashhur al Hurum is a holy month which is the connection between humans and God in the great pilgrimage conference and provides a favorable foundation for being on the divine path of avoiding war, hostility, hatred and conflict. In the interpretation of the verses about Ashhur al-Ḥurum there are several ethics of war in Islam. After reviewing and analyzing the problem, this research reached the following findings: first, An-Nasa is the postponement of the forbidden time from its place to alleviate the consequences of the prohibition. Second, three consecutive months and one separately for the Hajj and Umrah rituals, so one month is prohibited before the month of Hajj namely Dhulqo'dah because they refrain from war and the month of Dhulḥijjah they are forbidden because they perform Hajj in it and carry out worship and it is forbidden after that the following month namely Muharram to return home safely and Rajab is prohibited in the middle of the year to visit home and use it for those who come from far away to visit and return to their homeland safely. Third, humans do not give up weapons all at once during war and do not give up hostility and hatred. This is an opportunity for intellectuals and each ethnic group to hold an initial meeting by providing a dialogue platform and completing it comprehensively within a three-month period and returning peace and tranquility to society. The aim of this research is to construct and provide an Islamic religious perspective regarding the ethics of war, using analytical descriptive methods, this research answers Islamic (Qur'anic) problems. How do the verses of Ash'hur al-Ḥurum inform the ethical dimensions of war, and what the relevance of the construction connecting the message of Ash'hur al-Ḥurum's verses with the discourse on war ethics in general.